Marketing management in implementing digital branding and online marketing when facing the covid-19 pandemic - Mulatsih; Budi Utami; Indira, Christera Kuswahyu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
There is a downturn in the business and financial world due to the impact of the Covid-19 pandemic. This causes the need for an alternative form as a solution so that the products owned can still be marketed to consumers. Business people can do this by utilizing online marketing and digital branding to the fullest as a way of communication that can be done with consumers. This study aims to analyze how marketing and digital branding can be implemented during the Covid-19 pandemic. This research is qualitative, with data obtained from various research results and previous studies that are still related. This study found that online marketing strategies and digital branding were effective enough to be carried out during the Covid-19 pandemic. In addition, the implementation of online marketing and digital branding needs to be done optimally.